Body Odor Disgust Sensitivity Predicts Moral Harshness Toward Moral Violations of Purity - Liuzza, Marco Tullio; Olofsson, Jonas K.; Cancino-Montecinos, Sebastian; Lindholm, Torun (Frontiers in Psychology, 2019)
Detecting pathogen threats and avoiding disease is fundamental to human survival. The Behavioral Immune System (BIS) framework outlines a set of psychological functions that may have evolved for this purpose. Disgust is a core emotion that plays a pivotal role in the BIS, as it activates the behavioral avoidance motives that prevent people from being in contact with pathogens. To date, there has been little agreement on how disgust sensitivity might underlie moral judgments. Here, we investigated moral violations of “purity” (assumed to elicit disgust) and violations of “harm” (assumed to elicit anger). We hypothesized that individual differences in BIS-related traits would be associated with greater disgust (vs. anger) reactivity to, and greater condemnation of, purity (vs. harm) violations. The study was pre-registered (https://osf.io/57nm8/). Participants (N = 632) had to rate scenarios concerning moral wrongness or inappropriateness and regarding disgust and anger. To measure individual differences in the activation of the BIS, we used our recently developed Body Odor Disgust Scale (BODS), a BIS-related trait measure that assesses individual differences in feeling disgusted by body odors. In accordance with our predictions, we found that scores on the BODS relate more strongly to emotional reactions to Purity, as compared to Harm, violations. In addition, BODS relates more strongly to Moral condemnation than to perceived Inappropriateness of an action, and to the condemnation of Purity violations as compared to Harm violations. These results suggest that the BIS is involved in moral judgment, although to some extent this role sees to be specific for violations of “moral purity”, a concept that might be rooted in disease avoidance. Data and scripts to analyze the data are available on the Open Science Framework (OSF) repository: https://osf.io/tk4x5/. Planned analyses are available at https://osf.io/x6g3u/